DESAIN INSTRUKSIONAL (Kajian Terhadap Komponen Utama Strategi Instruksional dan Penyusunannya) - Batubara, Fitri Amaliyah (Lembaga Jurnal dan Seminar Universitas Pembangunan Panca Budi, 2018)
Instructional design is a process of planning or designing interesting, effective and efficient learning. This process becomes very important for educators, designers of learning and learners because it brings a great influence on the process of ongoing instructional activities and afterwards. The preparation of an instructional strategy becomes part of the instructional design with several important key components, such as instructional sequence activities, content outlines, instructional methods, media and instructional tools, and time.